1995
DOI: 10.1074/jbc.270.50.29910
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Molten Globule-like Conformations to Lipid Bilayers

Abstract: The effect of membrane binding on the structure and stability of several conformers of ␣-lactalbumin was studied by infrared spectroscopy, circular dichroism, and fluorescence spectroscopy. In solution, under experimental conditions where all conformers interact with negatively charged membranes, they show significant conformational differences. However, binding to negatively charged membranes, which causes considerable changes in the structure of these conformers, leads to a remarkably similar protein conform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(32 citation statements)
references
References 37 publications
4
28
0
Order By: Relevance
“…It was shown that α-LA also interacts with membranes containing negatively charged lipids such as phosphatidylglycerol. Interactions of several conformers of α-LA in aqueous solution with negatively charged large unilamellar vesicles (lecithin, 1,2-dioleoylphosphatidylglycerol, dipalmitoylphosphatidyl-glycerol,) were studied by CD, infrared spectroscopy, differential scanning calorimetry, and by content leakage experiments [ 205 , 206 , 207 ].…”
Section: Interactions Of α-Lactalbumin With Membranes and Hydrophmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that α-LA also interacts with membranes containing negatively charged lipids such as phosphatidylglycerol. Interactions of several conformers of α-LA in aqueous solution with negatively charged large unilamellar vesicles (lecithin, 1,2-dioleoylphosphatidylglycerol, dipalmitoylphosphatidyl-glycerol,) were studied by CD, infrared spectroscopy, differential scanning calorimetry, and by content leakage experiments [ 205 , 206 , 207 ].…”
Section: Interactions Of α-Lactalbumin With Membranes and Hydrophmentioning
confidence: 99%
“…Studies of interactions of α-LA with large unilamellar vesicles (lecithin, 1,2-dioleoylphosphatidylglycerol, dipalmitoylphosphatidylglycerol,) by CD, infrared spectroscopy, differential scanning calorimetry, and by content leakage experiments showed that the affinity of α-LA for negatively charged vesicles strongly depends on the conformational properties of the protein in solution and the native-like, calcium-bound, ordered conformations associate with bilayer through electrostatic interactions [ 205 , 206 , 207 ]. Ca 2+ -α-LA perturbs the membranes significantly only at pH 4.5, i.e., below the isoelectric point (pI) of the protein.…”
Section: Interactions Of α-Lactalbumin With Membranes and Hydrophmentioning
confidence: 99%
“…Artificial membranes may thus be useful to specifically address how HAMLET interacts with lipid bilayers. The protein constituent of HAMLET, HLA, is a 14.2-kDa milk protein known to interact with different lipid membranes, with partially unfolded states like molten globules having increased affinity for lipid bilayers [9], [10], [11], [12]. Native, folded HLA alone is not efficiently internalized by tumor cells and has no effect on cell viability.…”
Section: Introductionmentioning
confidence: 99%
“…Lactalbumin (8), retinol binding protein (38), colicin A (7), diphtheria toxin T-domain (5), StAR lipid binding domains (10), and barley nsLTP (12) are a few such proteins. The GLTP-fold represents both a novel motif among lipid binding/transfer proteins and a novel membrane interaction motif among amphitropic peripheral proteins that translocate to membranes during function (25).…”
Section: Discussionmentioning
confidence: 99%